Report of the Working Group on Phosphate deposits of India and their Utilisation - (:unkn) unknown (Planning Commission Government of India, 1970)
The 1970 report on Phosphate Deposits of India presents a comprehensive assessment of the country’s indigenous phosphate resources, their geological distribution, mining methods, and potential for agricultural and industrial utilization. Key phosphate deposits are located in Rajasthan, Uttar Pradesh, Himachal Pradesh, Tamil Nadu, and Bihar, with minerals such as apatite and phosphorites forming the core resources. The report emphasizes the critical role of phosphates in enhancing agricultural productivity through fertilizers, highlighting the dependence on imported phosphates due to limited domestic production in the 1960s. Operational challenges, including low-grade ores, remote locations, high iron content, and water scarcity for mining, necessitate beneficiation techniques and technological interventions to optimize yield. The report projects a growing demand for phosphatic fertilizers, estimating a requirement of 1.4 million tonnes by 1973–74, and underscores the economic advantages of developing local resources to reduce import dependence. Recommendations include systematic exploration, classification of deposits, research in phosphate processing, and international collaboration. Overall, the study advocates a strategic framework for sustainable utilization of phosphate resources to achieve agricultural self-sufficiency and long-term economic benefits for India.
Planning Commission New Delhi 1970
Keywords: Phosphate Deposits; India; Rock Phosphate; Fertilizer Production; Phosphorite; Mining Techniques; Agricultural Productivity; Beneficiation; Indigenous Resources; Geological Survey; Resource Utilization; Self-Sufficiency